Analysis of bed joint influence on masonry modulus of elasticity - Zavalis, R. (2014)
The means of determining the modulus of elasticity presented in technical literature often underestimate factors such as the influence of mechanical properties of the bed joint mortar and the influence of contact zone of the masonry unit and mortar on the elasticity modulus. Research carried out by the authors show that the modulus of elasticity of the bed joint considering influence of the contact zone (effective modulus of elasticity) is 3 to 25 times less than mortar modulus of elasticity, set by experimenting with samples in accordance with the requirements of the EN 1015-11 standard. The modulus of elasticity depends on the properties of mortar, masonry unit and bed joint thickness. This article discusses deformation properties of mortar in bed joints of calcium silicate block masonry. An analytical model determining mortar joint deformation properties is proposed, which considers a shift in mortar properties and the contact zone between mortar and the masonry unit. The masonry elasticity modulus values have been estimated applying the suggested method and comparing the results to the experimental values.